The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.4103/0974-8490.110545
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of bacterial endophytes from pharmaceutical agarwood-producing Aquilaria species

Abstract: Background:Resins and gums are used in traditional medicine and do have potential applications in pharmacy and medicine. Agarwood is the fragrant resinous wood, which is an important commodity from Aquilaria species and has been used as a sedative, analgesic, and digestive in traditional medicine. Endophytic bacteria are potentially important in producing pharmaceutical compounds found in the plants. Hence, it was important to understand which types of endophytic bacteria are associated with pharmaceutical aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 22 publications
1
19
0
Order By: Relevance
“…A method of producing agarwood resin by creating an artificial wound in the xylem of agarwood trees have been patented (Blanchette and van Beek (2005). Further discussions on various aspects of agarwood resin formation can be found in publications from Xu (2013), Mohamad (2010) and Bhore (2013).…”
Section: Discussionmentioning
confidence: 99%
“…A method of producing agarwood resin by creating an artificial wound in the xylem of agarwood trees have been patented (Blanchette and van Beek (2005). Further discussions on various aspects of agarwood resin formation can be found in publications from Xu (2013), Mohamad (2010) and Bhore (2013).…”
Section: Discussionmentioning
confidence: 99%
“…Latent pathogenicity of endophytes could be an economical source of local community and Aquilaria is a live example in this regard, which produces oleoresin after infection and enhances the value of tree in market (Barden et al, 2000; Pojanagaroon and Kaewrak, 2005; Chhipa et al, 2017). Various studies have been done on isolation of endophytes from Aquilaria species, such as Malyasian A. malaccensis (Mohamed et al, 2010; Bhore et al, 2013); Chinese A. sinensis (Gong and Guo, 2009; Tian et al, 2013); Thai A. crassna (Nimnoi et al, 2010); A. agallocha (Tamuli et al, 2000), and Indian A. malaccensis (Bhore et al, 2013). However, very few reports are available on the development of artificial infection by using these endophytes (Mitra and Gogol, 2001; Mohamed et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Tian et al (2013) reported the presence of Phomopsis, Botryosphaeria, Cylindrocladium , and Colletotrichum gloeosporioides species in wounded Aquilaria tree; and the presence of Alternaria, Mycosphaerella, Phoma, Ramichloridium , and Sagenomella species in the non-resinous tree internally. Bhore et al (2013) demonstrated the presence of endophytic bacteria and reported Bacillus pumilus to be a dominating species among 18 different types of bacteria. In another study, Huang et al (2015) reported the presence of distinct bacterial community in agarwood and non-agarwood plant of A. sinensis .…”
Section: Introductionmentioning
confidence: 99%
“…In order to meet the demand for agarwood and protect the wild Aquilaria trees, many countries with Aquilaria plantations also include research on agarwood cultivation and inoculation techniques in their strategy. Agarwood-producing Aquilaria species harbours 18 different types of culturable endophytic bacteria (Bhore et al 2013). Agarwood formation takes place in infected woody organs such as stem, branch and roots.…”
Section: Introductionmentioning
confidence: 99%